Detachment of a Guidewire Tip as an Intraoperative Complication during Revascularization of Chronic Coronary Artery Occlusion: A Clinical Case - M. A. Karimov; T. R. Ibragimov; O. V. Galimov; V. O. Khanov; S. I. Blagodarov (Креативная хирургия и онкология, 2024)
Introduction. Cardiovascular diseases occupy a leading position in the structure of mortality in the world. In particular, coronary heart disease causes mortality in 48% of cases among cardiovascular diseases. Surgical treatment of patients with coronary heart disease is aimed at eliminating stenotic or occlusive lesions in the coronary arteries by heart bypass and/or percutaneous coronary intervention with stenting. The success rate of the procedure accounts for about 85%. In the remaining 15%, revascularization fails to achieve its goal, which may be caused, among other things, by a pronounced calcification of the occlusive segment of the coronary artery. Aim: to demonstrate the development of one of complications after revascularization of chronic coronary artery occlusion and a method for its elimination. Materials and methods. The paper demonstrates a clinical case of an 86yearold patient with coronary heart disease treated in a nonemergency hospital. Coronary angiography revealed a multivessel lesion. Coronary artery bypass grafting was recommended after an intraoperative consultation with a cardiologist and a vascular surgeon. The next day, the patient underwent emergency coronary angiography in order to revascularize chronic occlusion. Results and discussion. The patient underwent attempted revascularization of chronic calcified occlusion, which resulted in such a complication as deformities and “detachment” of the distal tip of the guidewire. This complication was resolved with the help of a trifold snare and the creative and coldblooded thinking of the operating surgeon. Conclusion. The clinical case shows that, despite any encouraging statistical success rate, the operating surgeon should be ready for possible intraoperative complications. The key to solving this problem lies in the availability of modern medical tools for coronary interventions, as well as in relevant experience of an operating surgeon and creativity in making certain decisions.